Dissociation as a mediator of interpersonal trauma and depression: adulthood versus childhood interpersonal traumas3 - Seungyun Shim; Daeho Kim; Eunkyung Kim (BMC Psychiatry)
Abstract Extensive research has established that interpersonal trauma is related to depression and dissociation severity. Extending prior research, this study found that childhood and adulthood interpersonal traumas are related to depressive symptoms and examined the role of dissociative process as a mediator. Two hundred eighty-nine adult participants retrospectively reported on traumatic experiences and current symptoms of dissociation and depression, indicating that both childhood and adulthood interpersonal traumas are related to the severity of depression. However, childhood interpersonal trauma was associated with a higher level of dissociative symptoms. Moreover, it was suggested that dissociation serves as a pathway through which childhood interpersonal trauma influences depression, although this relationship was not observed for adulthood interpersonal trauma. In conclusion, this study highlights the potential role of dissociation in the development and maintenance of depression, particularly among individuals who have experienced childhood interpersonal trauma. These findings suggest that interventions targeting dissociation show potential for mitigating retrospective depression, especially for survivors of childhood interpersonal trauma.